On truncated generalized Gibbs ensembles in the Ising field theory - Essler, F; Mussardo, G; Panfil, M (IOP Publishing, 2017)
We discuss the implementation of two dierent truncated Generalized Gibbs Ensembles (GGE) describing the stationary state after a mass quench process in the Ising Field Theory. One truncated GGE is based on the semi-local charges of the model, the other on regularized versions of its ultra-local charges. We test the efficiency of the two different ensembles by comparing their predictions for the stationary state values of the single-particle Green's function G(x) = ⟨Ψ†(x)Ψ(0)⟩ of the complex fermion field Ψ(x). We find that both truncated GGEs are able to recover G(x), but for a given number of charges the semi-local version performs better.